(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The Meuraxa Green Tourism Park in Banda Aceh, which was established in the aftermath of the 2004 tsunami, embodies substantial ecological, societal, and spiritual significance as a public realm situated within a post-disaster reconstruction landscape. Nevertheless, its present state reveals a noticeable deterioration in terms of functionality and long-term sustainability, as evidenced by deteriorated infrastructure, insufficient levels of community engagement, and the gradual erosion of its cultural significance. This research critically assesses the sustainability of the park by employing Henri Lefebvre’s Theory of the Production of Social Space, a conceptual framework that interprets space as a socially constructed product shaped through three interrelated dimensions: spatial practice (perceived space), representations of space (conceived space), and representational space (lived space). A qualitative-descriptive method was applied using field observation, document analysis, and semi-structured interviews. Findings show that the park’s social and cultural sustainability remains weak. The spatial practice dimension reflects minimal social use; the representations of space dimension reveal top-down planning; and the representational space dimension shows diminished spiritual identity. The study concludes that the park’s sustainability depends on reproducing its social space through three strategies: physical revitalization, participatory social activation, and the restoration of spiritual and cultural meanings. These integrated approaches are essential to transform Meuraxa Park into a living, sustainable public space that embodies the resilience and spiritual identity of Acehnese society.